دور المصارف التقليدية في تمويل المنشآت الصغيرة والمتوسطة في سورية - الكفري, مصطفى; رمضان, محمد; البقاعي, أنس (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتناول هذا البحث بيان مفهوم المنشآت الصغيرة والمتوسطة في سورية، وأهميتها الاقتصادية، ومدى مساهمة المصارف التقليدية في تمويلها، والمسائل التي تحول دون وصول التمويل المطلوب إلى تلك المنشآت، حيث يرى كثير من الاقتصاديين أن تطوير المنشآت الصغيرة والمتوسطة وتشجيع إقامتها من أهم روافد عملية التنمية الاقتصادية والاجتماعية، وذلك باعتبارها منطلقاً أساسياً لزيادة الطاقة الإنتاجية من ناحية، والمساهمة في معالجة مشكلتي الفقر والبطالة من ناحية أخرى، ولذلك أولت دول كثيرة اهتماماً متزايداً بهذه المنشآت، وقدمت لها العون والمساعدة بمختلف السبل ووفقاً للإمكانيات المتاحة.أهم النتائج التي توصل إليها البحث:- وجود علاقة ارتباط قوية وطردية بين حجم التسهيل الائتماني المصرفي التقليدي العام والخاص الممنوح للمنشآت الصغيرة والمتوسطة والناتج المحلي الإجمالي.- تسهم هذه المنشآت في الاقتصاد الوطني بنسب مهمة في العمالة والتجارة الخارجية. - تشكّل حصة هذه المنشآت نسبة ضئيلة من إجمالي حجم التسهيلات الائتمانية الممنوحة من قبل المصارف التقليدية بشكليها العامة والخاصة.وتوصل البحث إلى مقترحات عدة أهمها: زيادة قدرة المنشآت الصغيرة والمتوسطة على الوصول إلى أدوات التمويل المختلفة في السوق، إضافة الى تقييم وتطوير فاعلية وحجم آليات التمويل المقدمة من قبل المؤسسات التمويلية، وتطوير نظام العمليات لدى المصارف المحلية بحيث يصبح أكثر مرونة، واعتماد تعريف وطني موحد للمنشآت الصغيرة والمتوسطة، و تنمية بيئة أعمال المنشآت الصغيرة والمتوسطة، بما يعزز ويدعم دورها في الاقتصاد الوطني.This research clarifies the concept of small and medium enterprises (SMEs), its economic importance and studies the contribution of conventional banks in the financing, and the issues that prevent the arrival of the required funding to those facilities. Whereas many economists believe that the development of SMEs and encouraging its establishment is one of the most important tributaries of the economic and social development. It considers as a basic starting point to increase production capacity on the one hand, and to contribute solving the problems of poverty and unemployment on the other hand. Therefore, many countries increase its interests in these enterprises, and provided them with help and assistance in various ways, according to available possibilities. The most important findings of the research: -There is a strong positive correlation between the size of the traditional public and private credit facility banking granted to SMEs and GDP.-These facilities contribute by an important proportion in employment and foreign trade to the national economy.-These facilities share form a small percentage of the total volume of credit facilities granted by existed conventional banks, public and private. The research found several proposals, including:-To increase SMEs' access to various financing instruments in the market, in addition to develop and evaluate the effectiveness and the size of the funding mechanisms provided by the financial institutions, and to develop the operation system of local banks so that the system becomes more flexible,-To adopt a national standard definition of small and medium enterprises.- To advance the business environment of SMEs, which by consequence contributes in promoting and supporting its role in the national economy.